GROWTH RESPONSES OF CATLA CATLA AND LABEO ROHITA UNDER MIXED EXPOSURE OF DIETARY AND WATER-BORNE HEAVY METALS VIZ. Cu, Cd AND Zn - F. Ameer; M. Javed; S. Hayat; S. Abdullah (Journal of Animal and Plant Sciences, 2013)
Growth performance of three age groups viz 60-, 90- and 120-day of two important culture-able indigenous fish species Thaila (Catla catla) and Rohu (Labeo rohita) was studied in glass aquaria under mix exposure of sub-lethal waterborne and dietary metals viz., Cu, Cd and Zn, keeping their control i.e. fish without metal exposure. This experimental trial was run for a period of 90 days at constant temperature (30 oC), pH (7.0) and hardness (200 mgL-1). The treated fish were fed with a diet having 35% digestible protein, 2.90 kcal/g digestible energy and sub-lethal concentration of each metal. All three age groups of both fish species showed statistically variable responses towards increase in wet weights, feed intake and feed conversion ratios under treated and control regimes against toxicity of metals. The 120-day treated fish revealed significantly better average weight gains than other two age groups. The control fish of both the species showed significantly higher weight gains than the treated fish. Three age groups of treated fish showed variable responses towards Cu, Cd and Zn stresses for their average feed intakes. The overall feed intake of control fish was significantly higher than that of treated fish. Feed conversion ratios (FCR) of both treated and control fish species varied significantly among various weeks of the experimental period and control fish exhibited significantly better FCR than the treated fish.
Keywords: acclimation; feed conversion ratio; sub-lethal; satiation; condition factor; LC; LD